Theranostics for MRI‐guided therapy: Recent developments. Issue 3 (3rd August 2021) - Zhang, Ziwei; Zhou, Feng‐Lei; Davies, Gemma‐Louise; Williams, Gareth R.
Abstract: Recent advances in bioimaging, biochemistry, and bioinformatics have facilitated the development of personalized and precision medicine. Theranostics, combining imaging modalities and therapeutic agents, have garnered a lot of attention in this context, owing to their potential to monitor and control treatment for individual patients. A promising strategy to achieve this goal involves the development of therapy guided by magnetic resonance imaging (MRI). MRI has a high degree of soft tissue contrast, low invasiveness, high depth of penetration and good spatial resolution. MRI‐guided therapy could thus allow precise and time‐resolved assessment of disease conditions and therapeutic progression. This article will give a brief introduction to the principles of MRI, and describe recently developed strategies to produce MRI‐guided therapies. A number of theranostics based on T 1, T 2, or chemical exchange saturation transfer (CEST) MRI have been explored to track the route of drug carriers in vivo and image diseased tissue so as to enhance bioavailability, overcome complex delivery barriers, and assess therapeutic responses. In addition, the integration of thermal therapy and MRI imaging offers a strategy to noninvasively identify target areas, plan treatment, and provide real‐time assessment of the efficacy of tumor ablation. We also discuss advances in intelligent nanoparticles combining small molecule drugs, thermal treatment and multimodal imaging, arguing that these multifunctional agents can further improve therapeutic outcomes. Abstract : This paper first describes the theory of MRI and its utility for imaging in vivo. It then reviews recently developed theranostics combining MRI‐based diagnosis (e.g., T 1 /T 2, CEST MRI) and an anticancer therapeutic agent for applications in chemotherapy and thermal therapies.